O conceito de mito na obra de Roland Barthes: desdobramentos e atualidade - Padilha, Conrado Valle de Queiroz (2014)
The cardinal purpose of this work is to present the Barthesian concept of myth as per its definition in Mythologies. It is also an attempt to follow how it unfolds in the work of Roland Barthes through a small set of selected texts: Writing Degree Zero, Mythologies, Elements of Semiology, L obvie et l obtus, Roland Barthes by Roland Barthes, and Camera Lucida. This research implies in handling the concept of connotation, through which Barthes defines the myth as an ultra-signification message. We here play with the hypothesis of the concept of studium, belatedly introduced in Camera Lucida, as a reformulation of the myth in the photography field, since Barthes himself sees in it the same characteristic effect of the connotative phenomenon. In such a manner, the corpus of this research is given by the author s mentioned texts; for its convenient aspect, it is also added of the repertoire of images offered by the researcher Jacqueline Guittard and her Mythologies illustrées, which recaptures and expands the edition known so far; the images of Camera Lucida are also added to it. The relevance of this research is tied to the possibility offered by Barthes oeuvre to criticize the mass communications in a historic and semiotic perspective, always paying attention to the work of the signifier